Recruitment and Motivation Effects on EMIS Operator Performance in Madrasahs of Tana Toraja and North Toraja - Yusriyani Ningsih; Rustan Santaria; Hisbullah Hisbullah (International Journal of Educational Administration, Management, and Leadership, 2024)
This study investigates the influence of recruitment and work motivation on the performance of Education Management Information System (EMIS) operators in madrasahs located in Tana Toraja and North Toraja, Indonesia. Utilizing a quantitative survey design, data were collected through structured questionnaires distributed to all active EMIS operators (n = 7) in the region. The findings reveal that both recruitment and motivation significantly and positively affect operator performance, with regression analysis confirming their individual and combined contributions. Recruitment practices based on objective and competency-oriented criteria were found to enhance data accuracy and operational efficiency, while both intrinsic and extrinsic motivation contributed to greater task commitment and consistency. The study also confirms that the interaction between these two variables generates a synergistic effect, emphasizing their strategic importance in human resource management within Islamic educational institutions. These results suggest that improving recruitment procedures and strengthening motivational support can lead to more effective educational data governance and higher institutional performance. Recommendations are proposed for policy and practice to institutionalize transparent recruitment systems and sustainable motivational frameworks in madrasah education.